Forcing of recent decadal variability in the Equatorial and North Indian Ocean. Issue 9 (13th September 2016) - Thompson, P. R.; Piecuch, C. G.; Merrifield, M. A.; McCreary, J. P.; Firing, E.
Abstract: Recent decadal sea surface height (SSH) variability across the Equatorial and North Indian Ocean (ENIO, north of 5°S) is spatially coherent and related to a reversal in basin‐scale, upper‐ocean‐temperature trends. Analysis of ocean and forcing fields from a data‐assimilating ocean synthesis (ECCOv4) suggests that two equally important mechanisms of wind‐driven heat redistribution within the Indian Ocean account for a majority of the decadal variability. The first is the Cross‐Equatorial Cell (CEC) forced by zonal wind stress curl at the equator. The wind stress curl variability relates to the strength and position of the Mascarene High, which is influenced by the phase of the Indian Ocean Subtropical Dipole. The second mechanism is deep (700 m) upwelling related to zonal wind stress at the equator that causes deep, cross‐equatorial overturning due to the unique geometry of the basin. The CEC acts to cool the upper ocean throughout most of the first decade of satellite altimetry, while the deep upwelling delays and then amplifies the effect of the CEC on SSH. During the subsequent decade, reversals in the forcing anomalies drive warming of the upper ocean and increasing SSH, with the effect of the deep upwelling leading the CEC. Key Points: Recent decadal variability reflects wind‐driven redistribution of heat within the Indian Ocean The Cross‐Equatorial Cell forced by equatorial wind stress curl contributes to decadal change Forcing related to equatorial zonal wind stress contributes by driving deep upwelling